PEMANFAATAN MEDIA PEMBELAJARAN DI SEKOLAH (Studi Kasus Di Kelas Rendah SD Negeri 1 Pagar Alam) - Septa Olpidiya Siska (DIADIK, 2021)
The purpose of this research is to describe media use planning, describe the media utilization process, evaluate and follow up on the use of low-grade learning media at SD Negeri 1 Pagar Alam. The method used in this research is descriptive qualitative method, data collection techniques using interviews, observation and documentation. The research subjects who became the population in this study were low class (grades 1,2 and 3) while the sample in this study were 3 respondents who came from their respective class teachers. The results showed that the planning, process, evaluation and follow-up in the use of instructional media had been implemented properly. The delivery of teaching materials using learning media is very helpful for students in understanding the material presented by the teacher